Density Functional Theory Study of Interface Interactions in Hydroxyapatite/Rutile Composites for Biomedical Applications; Journal of Physical Chemistry C; Vol. 121, iss. 29 - Tsyshevsky R. V. Roman; Grubova I. Yu. Irina Yurievna; Surmeneva M. A. Maria Alexandrovna; Huygh S. Stijn; Surmenev R. A. Roman Anatolievich; Neyts E. C. Erik (2017, 2017)
Title screen